Murine neonatal cardiac B cells promote cardiomyocyte proliferation and heart regeneration - Yong Tan; Xuewen Duan; Bo Wang; Xingguang Liu; Zhenzhen Zhan (npj Regenerative Medicine, 2023)
Abstract The irreversible loss of cardiomyocytes in the adult heart following cardiac injury leads to adverse cardiac remodeling and ventricular dysfunction. However, the role of B cells in cardiomyocyte proliferation and heart regeneration has not been clarified. Here, we found that the neonatal mice with B cell depletion showed markedly reduced cardiomyocyte proliferation, leading to cardiac dysfunction, fibrosis scar formation, and the complete failure of heart regeneration after apical resection. B cell depletion also significantly impaired heart regeneration and cardiac function in neonatal mice following myocardial infarction (MI). However, B cell depletion in adult mice suppressed tissue inflammation, inhibited myocardial fibrosis, and improved cardiac function after MI. Interestingly, B cell depletion partially restricted cardiomyocyte proliferation in adult mice post-MI. Single-cell RNA sequencing showed that cardiac B cells possessed a more powerful ability to inhibit inflammatory responses and enhance angiogenesis in the postnatal day 1 (P1) mice compared with P7 and adult mice. Besides, the proportion of cardioprotective B cell clusters with high expression levels of S100a6 (S100 calcium-binding protein A6) and S100a4 (S100 calcium-binding protein A4) was greatly decreased in adult heart tissues compared with neonatal mice after cardiac damage. Thus, our study discovers that cardiac B cells in neonatal mice are required for cardiomyocyte proliferation and heart regeneration, while adult B cells promote inflammation and impair cardiac function after myocardial injury.